Does Exposure to Primary Care Early in the Didactic Phase of the Physician Assistant (PA) Curriculum Influence Field Choice Post-Graduation?. (September 2020) - Gruver, Michelle; Gamber, Michelle
Background: Over the past 10 years, the nation has witnessed a significant increase in the number of physician assistant (PA) education programs. Primary care shortages throughout the United States have reached a staggering deficiency. The purpose of this project was to expand the primary care workforce in the Commonwealth of Virginia by increasing exposure to primary care setting early in the academic didactic year of physician assistant schooling. Methods: This innovative research project originated in 2017 and was inclusive of PA students ranging from 20 to 44 years of age, across multiple demographics, conducted during the first year of didactic studies. This cross-sections study examined a total size of 115 students over from three different cohort years that participated in the free medical clinic completed a pre/post exposure survey. Results: This study highlighted that an increased exposure to primary care in the early didactic phase of physician assistant graduate studies yielded a moderate increase in the interest to pursue a career in primary care upon graduation. Throughout the 2016 to 2017, 2017 to 2018, and 2018 to 2019 academic cohorts, 19% more from baseline indicated at the end of their primary care experience that they were more likely to practice in the field of primary care following the free medical clinic experience. Conclusions: This study demonstrates a positive influence of early exposure to primary care for Physician Assistant students with the increased affinity to practice in the field upon graduation and has set a foundation for continuation of data collection in future PA cohorts.